2020
DOI: 10.3390/nu13010011
|View full text |Cite
|
Sign up to set email alerts
|

Facial EMG Activity Is Associated with Hedonic Experiences but Not Nutritional Values While Viewing Food Images

Abstract: The physiological correlates of hedonic/emotional experiences to visual food stimuli are of theoretical and practical interest. Previous psychophysiological studies have shown that facial electromyography (EMG) signals were related to subjective hedonic ratings in response to food images. However, because other data showed positive correlations between hedonic ratings and objective nutritional values of food, whether the facial EMG reactions to food images could reflect the hedonic evaluation or nutritional as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…Our results also revealed that the ratings of liking, wanting, and valence were not significantly associated with zygomatic major EMG activity with and without adjustment for masticatory EMG and acceleration, which is consistent with previous findings [8]. Although the results of several previous studies testing non-eating tasks revealed that subjective valence ratings were associated with EMG activity measured from both the corrugator supercilii and zygomatic major muscles (e.g., [12]), some studies found that subjective ratings were associated with EMG for only one of these muscles [14,59]. Taken together, our results imply that subjective hedonic experiences during eating are more evidently associated with EMG signals measured from corrugator supercilii EMG compared with zygomatic major EMG.…”
Section: Discussionsupporting
confidence: 88%
“…Our results also revealed that the ratings of liking, wanting, and valence were not significantly associated with zygomatic major EMG activity with and without adjustment for masticatory EMG and acceleration, which is consistent with previous findings [8]. Although the results of several previous studies testing non-eating tasks revealed that subjective valence ratings were associated with EMG activity measured from both the corrugator supercilii and zygomatic major muscles (e.g., [12]), some studies found that subjective ratings were associated with EMG for only one of these muscles [14,59]. Taken together, our results imply that subjective hedonic experiences during eating are more evidently associated with EMG signals measured from corrugator supercilii EMG compared with zygomatic major EMG.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the variations in facial muscles and brain activities are linked. The conducted investigation in this study is more advanced comparing to the works [1][2][3][4][5][6][7] which only analyzed the facial muscles' reaction without linking to brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers investigating facial muscle activity under varying conditions have reported plenty of prior works in the available literature. For instance, the reported studies that monitored EMG signals in decompression operation [1], analyzed EMG signals to recognize intensive valence and arousal affective [2], evaluated the influence of visual [3], emotional [4], and auditory [5] stimuli on EMG signals; judged smile authenticity by analysis of EMG signals [6], and evaluated the alterations of facial muscle activity in aging [7], are worthy of being mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Applications are reported from fine arts but rarely from consumer behavior. For tasting food products or looking at pictures of food products, studies using fEMG have shown that the activity of selected facial muscles correlates with self-reported hedonic responses [55,56].…”
Section: Observational Methods Using Technical Equipment In a Laborat...mentioning
confidence: 99%